Enhancing the Photocatalytic Activity of SnO2-TiO2 and ZnO-TiO2 Tandem Structures Toward Indoor Air Decontamination - Enesca, Alexandru (Frontiers in Chemistry, 2020)
ZnO-TiO2 and SnO2-TiO2 tandem structures were developed using the doctor blade technique. It was found that by employing organic hydrophilic and hydrophobic as additives into the precursor it is possible to tailor the film density and morphology with direct consequences on the photocatalytic activity of the tandem structures. The highest photocatalytic efficiency corresponds to ZnO-TiO2 and can reach 74.04% photocatalytic efficiency toward acetaldehyde when a hydrophilic additive is used and 70.93% when a hydrophobic additive is employed. The snO2-TiO2 tandem structure presents lower photocatalytic properties (61.35 % when the hydrophilic additive is used) with a constant rate reaction of 0.07771 min−1.